(3YbGFO GdfSajs - (3GdfSaj, CHh MaU, fLe GdOjf, YeQ Hf eMeO CMeO, J (B537 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd Cgd GdMb (B: (3MbGFb GdCTjGA KGHJI hGdYde HgG eJMbb NdGaG ddShaSWGFjI hCSHGH GdYde ddNdb KdGKI (B: (3GdMhGS GdSdjeI hGdNHQ GdUGOb hGdYbds
(3BNQgG (B:s
(3hWdhY GdTeS ef eZQHgG agh Mb hGdeLJgO bO jNWF hbO jUjH hQSd GdHTQ CaVd ef QSd GdedGFcI hQSd GdedGFcI CaVd ef YGeI GdHTQ hYGeI GdHTQ ef GdeDefjf CaVd ef YGeI GdedGFcIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 60s
(3eYLe GdeDdajf (B2 / 571s
(3cTa GdXfhf (B2 / 1145s
(3TPQGJ GdPgH (B4 / 115s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds